Middle East 101 : a beginner's guide for deployers, travelers, and concerned citizens - Aboul-Enein, Youssef H.; Stanik, Joseph T. (Naval Institute Press, 2019)
This work answers 101 essential questions on the Middle East, Islam, the Arab Spring, al-Qa'ida, and ISIS for those wanting to begin an intellectual immersion into the complexities of the region from pre-biblical times to the post-Arab Spring era.